Anemia and associated factors among school-age children in Filtu Town, Somali region, Southeast Ethiopia - Gutema, Bekele (BioMed Central, 2014)
BACKGROUND: Anemia is one of the major public health problems affecting more than half of school-age children in developing countries. Anemia among children has been conclusively seen to delay psychomotor development, poor cognitive performance, impaired immunity and decrease working capacity. The purpose of this study is to determine the prevalence and associated factors of anemia among school-age children in Filtu Town, Somali region, Southeast Ethiopia. METHODS: A community based cross-sectional study was conducted from July to August, 2013 in Filtu Town. A total of 355 school-age children between 5–15 years old were included in the study. Socio-demographic data were obtained from each participant using structured questionnaire. Hemoglobin concentration was determined by HemoCue 201(+) photometer (HemoCue, Angelholm, Sweden) analyzer. Hemoglobin values below 11.5 g/dl and 12 g/dl were considered as anemic for age ranges of 5–11 and 12–15 years, respectively. Anthropometric data were taken from each study participant. Peripheral blood film and stool examination were done for hemoparasite and intestinal parasite screening, respectively. Data were analyzed using SPSS version 16.0. RESULTS: Over all, prevalence of anemia was found to be 23.66%. The vast majority (73.81%) of the anemic children had mild anemia. Moderate and severe anemia accounted for 25% and 1.19% of the anemic children, respectively. Being from a family with low income (AOR = 9.44, 95% CI: 2.88, 30.99), stunted (AOR = 5.50, 95% CI: 2.83, 10.72), underweight (AOR = 2.07, 95% CI: 1.06, 4.05) and having intestinal parasite infection (AOR = 2.99, 95% CI: 1.05, 8.46) were identified as associated factors for anemia. CONCLUSION: Anemia is a moderate public health problem in school-age children for the study area. Interventions targeting nutritional deficiencies and parasitic infections are recommended.